1998
DOI: 10.1038/sj.bmt.1701190
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A-induced graft-versus-host disease following autologous bone marrow and stem cell transplantation in hematological malignancies of childhood

Abstract: Summary:Cyclosporin A (CsA) can induce graft-versus-host disease (GVHD) following autologous bone marrow transplantation (ABMT) and autologous peripheral blood stem cell transplantation (APBSCT) in adults. We investigated whether GVHD can be induced following ABMT and APBSCT in childhood, and which cells are involved in the pathogenesis of this syndrome. We conducted a prospective study of 20 children and adolescents with hematological malignancies receiving CsA after ABMT and APBSCT. Skin biopsies were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Recently, the results of a study on CsA-induced aGVHD following ABMT in childhood malignancies suggested that aGVHD can be safely and reproducibly induced by 1.5 mg/kg/day of CsA administered intravenously for 28 days. 16,29,30 Our results confirm this finding since CsA was well tolerated and no grade III/IVtoxicity was reported with the use of CsA. Furthermore, hematopoietic recovery was not delayed by the administration of CsA during the first 28 days post-myeloablation and ABMT.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Recently, the results of a study on CsA-induced aGVHD following ABMT in childhood malignancies suggested that aGVHD can be safely and reproducibly induced by 1.5 mg/kg/day of CsA administered intravenously for 28 days. 16,29,30 Our results confirm this finding since CsA was well tolerated and no grade III/IVtoxicity was reported with the use of CsA. Furthermore, hematopoietic recovery was not delayed by the administration of CsA during the first 28 days post-myeloablation and ABMT.…”
Section: Discussionsupporting
confidence: 78%
“…As has been previously demonstrated in animal and human clinical studies, an autologous GVHDlike reaction (aGVHD) may be induced by CsA. 16,29 Of our 24 patients, eight developed a skin rash, three were biopsied and one was positive for aGVHD. The other seven rashes were consistent with grade II clinical skin aGVHD.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Although histocompatibility differences are thought to initiate the anti‐host response of the graft, a syndrome with pathology identical to GVHD can occur after autologous bone marrow transplantation (BMT) (Thien et al , 1981). This syndrome, termed autologous or syngeneic GVHD, occurs spontaneously in 5–10% of patients receiving an autologous or syngeneic HSCT (Hood et al , 1987; Byrne et al , 1997) and may be induced by the administration of cyclosporin A (CyA) after autologous HSCT in animals (Glazier et al , 1983; Bryson et al , 1989) and humans (Jones et al , 1989; Talbot et al , 1990; Carella et al , 1991; Kennedy et al , 1993; Yeager et al , 1993; Pati et al , 1996; Giralt et al , 1997; Gruhn et al , 1998). This syndrome has notable anti‐tumour activity in animal studies (Geller et al , 1989; Charak et al , 1992a; Bryson et al , 1999) and there is also some indication of an anti‐tumour effect in humans (Byrne et al , 1997).…”
mentioning
confidence: 99%